2017
DOI: 10.1108/ijccsm-08-2016-0114
|View full text |Cite
|
Sign up to set email alerts
|

Learning lab on disaster risk management for sustainable development (DRM-SD)

Abstract: Purpose-A series of "learning lab" projects on disaster risk management for sustainable development (DRM-SD) have been accomplished from 2014 to 2016 in Malaysia, Vietnam, Lao PDR and Cambodia by the Centre for Global Sustainability Studies. The project is designed for professionals from the disaster risk management field to encourage integration of sustainable development (SD) concerns into the larger planning framework for DRM. As a case study for capacity building (CB) evaluation, the central purpose of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…Thus, a learning lab is either a method of intervention, a program (Bal et al, 2018), a physical (Carron et al, 2018 or digital (Zinger et al, 2017) space, often located in the library of the university (Cartier, 2014). In terms of objectives, we found the same diversity: a learning lab is dedicated to address educational or social challenges such as racism and equity (Bal et al, 2018) and natural hazards (Shabudin et al, 2017). Some researchers consider that a learning lab aims at training students in general or improving the students' (Brehm & Guenzel, 2018;Kift, 2017) or teachers' (Zinger et al, 2017) digital skills.…”
Section: Learning Lab Towards a Definitionmentioning
confidence: 84%
“…Thus, a learning lab is either a method of intervention, a program (Bal et al, 2018), a physical (Carron et al, 2018 or digital (Zinger et al, 2017) space, often located in the library of the university (Cartier, 2014). In terms of objectives, we found the same diversity: a learning lab is dedicated to address educational or social challenges such as racism and equity (Bal et al, 2018) and natural hazards (Shabudin et al, 2017). Some researchers consider that a learning lab aims at training students in general or improving the students' (Brehm & Guenzel, 2018;Kift, 2017) or teachers' (Zinger et al, 2017) digital skills.…”
Section: Learning Lab Towards a Definitionmentioning
confidence: 84%
“…Moreover, it less considered about time planning for operations and less of experience of humanitarian aids collaboration. Altay and Labonte summary integrated complexity-information flow impediment in humanitarian information management and exchange [14].…”
Section: Resultsmentioning
confidence: 99%
“…动型创新转变的工作方式 [58] [59] 。因此,"生活实验室"常被应用于行业 市场评估领域,以使产品和服务实现快速商业化 [59]~ [62] 。 然而,"生活实验室"的出现和发展恰好可以协调各利益相关方 之间复杂甚或充满矛盾的诉求。于是,"生活实验室"概念逐渐扩展 到了包括可持续能源和医疗在内的其他领域 [63] 。在社会科学领域,"生 活实验室"概念最早出现在20世纪90年代的一门大学课程概述中,修 读这门课程的学生会在市中心附近开展实际落地项目 [64] 。由此可见, "生活实验室"包含技术和社会两个层面 [65] 。 近年来,"生活实验室"作为一种参与过程被应用于景观规划领 域,以使利益相关者参与到景观解决方案(如NBS)的共同规划、设计 和验证过程中 [65] 。不同于传统的多方参与,"生活实验室"在整个规划 过程中仅赋权于一个相对稳定的利益相关者团体 [66]~ [68] 。桑德拉•福梅 斯特等 [69] 发现,迄今为止,大多数利用"生活实验室"进行景观规划的 研究均通过所谓的"城市生活实验室"解决城市问题 [70] 。尽管"生活 实验室"的要素(如合作生产 [71] 或合作学习 [72] )已被用于减灾预警中, 但其应用潜力尚未被充分挖掘。尽管"生活实验室"拥有丰富的外延 (表2),但它们都呈现出某些一致的核心特征(表3)。 "生活实验室"包括几种不同的参与步骤(表4),如萨坡•利米 宁 [73] 将其分为4个步骤(框架一),汉斯•谢弗等 [74] 和哈维尔•加西 亚•古兹曼等 [75] 提出5个步骤(框架二),克里斯•施特恩等 [68] 列出8个…”
Section: 欧盟委员会 European Commissionunclassified
“…Sandra Fohlmeister et al [69] found that to date, most studies using the Living Lab for landscape planning to address adaptation and mitigation in urban settings using so-called "Urban Living Labs" (ULLs) [70] . While elements of the Living Lab, such as co-production [71] and co-learning [72] , have been applied in the context of disaster risk reduction, full applications of the Living Lab are lacking. Despite these diverse definitions (Table 2), the Living Lab presents consistent core characteristics ( Table 3).…”
Section: 欧盟委员会 European Commissionmentioning
confidence: 99%
See 1 more Smart Citation